2018
DOI: 10.1038/s41598-018-22896-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection Increases Risk of Gallstone Disease in Elderly Chinese Patients with Chronic Liver Disease

Abstract: We investigated possible links between the etiology of liver disease and gallstone risk in Chinese patients with chronic liver disease (CLD). We compared the outcomes of 267 Chinese CLD patients with gallstones and those of a control group of 1,015 CLD patients without gallstones. Logistic regression analyses adjusting for demographic features and other gallstone risk factors revealed that liver cirrhosis increased the risk of gallstone development twofold [adjusted odds ratio (AOR); 95% confidence interval (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In recent years, helicobacter pylori, HBV, HCV, Clonorchis sinensis, ascaris, and schistosomiasis have also been found to increase the risk of recurrence of choledocholithiasis. (47,51) Intervention factors Lifestyle Some studies have shown that a typical diet high in calories, cholesterol, fatty acids, or carbohydrates increases the risk of gallstones. (18,21,84) Physical activity reduces biliary cholesterol saturation by increasing HDL-C (23) and by affecting plasma TG and insulin release (82).…”
Section: Biological Factorsmentioning
confidence: 99%
“…In recent years, helicobacter pylori, HBV, HCV, Clonorchis sinensis, ascaris, and schistosomiasis have also been found to increase the risk of recurrence of choledocholithiasis. (47,51) Intervention factors Lifestyle Some studies have shown that a typical diet high in calories, cholesterol, fatty acids, or carbohydrates increases the risk of gallstones. (18,21,84) Physical activity reduces biliary cholesterol saturation by increasing HDL-C (23) and by affecting plasma TG and insulin release (82).…”
Section: Biological Factorsmentioning
confidence: 99%
“…It has been proven that changes in bile acid composition and increased nucleation of bile combined with decreased motility of the gallbladder may contribute to the development of gallstones in patients with liver cirrhosis. Thus, cirrhotic patients have a higher incidence and prevalence of gallstones [11][12][13][14]. The portal vein diameter and hypersplenism are risk factors for developing gallstones in patients with cirrhosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that changes in bile acid composition and increased nucleation of bile combined with decreased motility of the gallbladder may contribute to the development of gallstones in patients with liver cirrhosis. Thus, cirrhotic patients have a higher incidence and prevalence of gallstones [12][13][14][15] . The portal vein diameter and hypersplenism are risk factors for developing gallstones in patients with cirrhosis 15 .…”
Section: Discussionmentioning
confidence: 99%